Factors affecting local tourist decisions towards National Park case study: Gunung Gading, Lundu, Sarawak / Hajeline Blon - Blon, Hajeline (2005)
The number of local tourists who visit Gunung Gading National Park is not very encouraging. The purpose of this study is to identify the factors affecting local tourist decision towards national park, case study of Gunung Gading National Park, Lundu Sarawak. The methods of survey that had been used are questionnaires, personal interviews and observation. From 384 questionnaires that had been distributed, only 249 are managed to be collected which the respondents are from Kuching City and Gunung Gading National Park. Respondents are from different range of age and there are from different background of studies, level of income, race and interest. The respondents are aware of Gunung Gading National Park but the culture of local people is spending time at home during holidays instead of go outing at recreational or national park. The factor that affecting the number of tourist is lack of promotion used by the Sarawak Forestry Cooperation and the strategies to be used is by improving the promotion tools.